Tecnologie libere ed open source per la consultazione e l’elaborazione di dati territoriali ed idrometeorologici in applicazioni web-based - Casadei, Stefano; Bellezza, Michele; Casagrande, Luca; Pierleoni, Arnaldo; Marchesini, Ivan (GEOmedia, 2009)
Open source and free technologies for spatial and hydrometeorological data referencing and managing in web based applications In the field of water resources management, it is more important to operate at territorial scales larger than the administrative ones to take into consideration the entire watershed. This, on one hand, requires a wider sharing of the initial hydraulic data, while on the other, the larger territorial dimension, the social and environmental issues, bring up the need of more integrated approaches and of a wider integration between Hydrological data and territorial information. The WRME project has been developed as an SDSS to share data, models and results via a WEB interface in order to put around the same integrated system all the stakeholders involved.